Rethinking Communication Geographies: Geomedia, digital logistics and the human condition - Jansson, André (Cheltenham Edward Elgar, 2022)
Timely and original, Rethinking Communication Geographies explores the human condition under digital capitalism, depicting an environment in which digital logistics have taken centre stage in day-to-day life and culture. The book responds to a pressing need to address questions of human autonomy and security, as well as the social power relations of the platform economy, in a world in which media and space have become increasingly entangled.
Keywords: Geography; Planning and tourism; Communication